Mergawe: A Picture of Changing Women's Tradition - Moh. Faiz Maulana (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
This research focuses on women's efforts in placing themselves in the right position. In the midst of changing times that are so fast and open, women are faced with a feeling of dilemma. On the one hand, women are limited by traditions that always place them in the domestic sphere, which is commonly known as konco wingking. On the other hand, changing times or modernization has given women the freedom to enter the public sphere. Through moderation of the tradition, women in Paciran have managed to get out of their dilemma. They can maintain their traditions and identity as Javanese women and can create new traditions by accepting them as workers. Tradition moderation has also changed the meaning and view of the konco wingking tradition, which so far has only been considered a "place of origin" with its domestic role; macak, masak, manak, but also a "place of return" the tradition that becomes the foothold of women's life in viewing social reality; community, and family. This research was conducted on women working nguplik in a village in Paciran, Lamongan, East Java. Nguplik is the job of separating the ripe crab shell or skin from the meat to be sold and processed into food and cosmetics. Nguplik is carried out by individuals and or a group of women. This study uses a qualitative method with a case study approach, with the data collection process using interviews and observations. To analyze the data we used the theory of cultural sociology. The finding of this research is the acceptance of women as workers.